Safety and Efficacy of Rivaroxaban-Aspirin Combination Compared to Aspirin Monotherapy on Lower Peripheral Artery Disease after Revascularization: Systematic Review and Meta-analyses - Thio, Robby E; Pratama, Dedy (UI Scholars Hub, 2024)
Introduction. Currently, single antiplatelet treatments using aspirin or clopidogrel are recommended for post-revascularization peripheral artery disease (PAD) patients. However, a recent study suggested that a combination of rivaroxaban and aspirin was more favorable to use. We conducted a systematic review to determine the efficacy and safety of rivaroxaban and aspirin combination compared to aspirin alone. Method. A systematic review conducted based on the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) protocol. Search using keywords was conducted on Cochrane, PubMed, Scopus, EBSCOHost, and Google Scholar. Inclusion and exclusion criteria were applied. Selected studies were appraised using the Cochrane risk of bias tool v.2 for inclusion. The studies included were extracted for characteristics and outcomes. Outcomes were analyzed qualitatively and quantitatively. We used a fixed- or random-effect model to determine the pooled ratio per appropriate. A 95% confidence interval and p-value of 0.05 and below were used as indicators of statistical significance. Results. Two multicentered, randomized controlled studies were included after searching. They were appraised with a low risk of bias. Both studies showed greater primary effectivity outcomes in the combination group and improvements in major bleeding risk. The quantitative analysis found lower PAD complications rate (OR = 0.79; 95% CI = 0.66–0.95), which included myocardial infarction, stroke, cardiovascular death, and acute limb ischemia. The combination group provided lesser primary (OR = 1.32; 95% CI = 1.06–1.67) and secondary (OR = 1.47; 95% CI = 1.19–1.84) safety outcomes. Conclusion. A combination of rivaroxaban and aspirin provided better clinical outcomes in post-revascularization PAD patients. However, this combination should be used carefully as this yields a more significant risk of bleeding in the population.